(untitled) (SAARC Journal of Agriculture, 2023)
An experiment was conducted at the Vegetable Research field of Horticulture Research Centre Division, Bangladesh Agricultural Research Institute, Gazipur, Bangladesh, during October 2018 to February 2019to find out the effect of plant spacingand mulchon yield and yield attributes of squash. The experiment comprised two sets of treatments viz., (a) Plant spacing:(i) 1 m × 0.8 m (S1); (ii) 1 m × 1 m (S2) and 1m × 1.5 (S3) and (b)Mulch: (i) No mulch (M1); (ii) Straw mulch(M2) and (iii)Polythene mulch (M3) in a randomized complete block design (RCBD) with three replications. The variety BARI squash-1 was used in this experiment. The results showed that 1m × 1.5 plant spacing showed significantly the highest yield attributes and quality parameters but 1m × 1 m plant spacing showed significantly the highest yield ha-1. Polythene mulch showed significantly the highest fruit plant-1, yield plant-1 and yield ha-1. Fruit size, individual fruit weight and quality parameter did not show any significant difference irrespective of mulching. The interaction between plant spacing and mulch was significant for yield and quality parameters. Based on the study results it is concluded that maximum yield (50.20 t ha-1) was achieved through 1m × 1 m plant spacing with polythene much but higher TSS and vitamin C was found through 1m × 1.5 m plant spacing with polythene much. SAARC J. Agric., 21(2): 251-261 (2023)